Peranan Badan Arbitrasi Nasional Indonesia dalam Menyelesaikan Sengketa Bisnis di Indonesia - Muhammad Faisal (Fakultas Hukum Universitas Mataram, 2015)
The purpose of this research is to determine and understand the role of Indonesia Arbitration Centre (BANI) in resolving business disputes in Indonesia and procedure in Indonesia Arbitration Centre to dispute business settlement. Method of approach in this research use Legislation approach (statute approach), conducted by reviewing laws and regulations relating to the issues discussed. Conceptual Approach, examines the views/concept of the experts people to the issues of discussed: Based on above, the results of this reasearch are: Indonesia Arbitration Centre is currently favored to dispute resolution by the parties who are in business, It is seen from the development of BANI in settlement the business dispute both after and before enactment of The Act Number 30 of 1999 on Arbitration and Alternative Dispute Settlement. Dispute Settlement procedures at BANI can be done by submission of application and registration, defendant feedback, foration the arbitral tribunal, arbitration reconnaissance, determination the arbitration decision and the submission and registration of the arbitration decision.